Valorization of Rice Panicle Straw and Watermelon Rind as an Innovative Medium for Eco-FriendlyProduction of SCOBY Biofilm - Priyadi, Sapto; Wiyono; Haryuni; Ramadhan, Karunia Irfan; Nugroho, Benny (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
The valorization of agro-food waste represents a promising pathway toward sustainable bio-based materials. This study aimed to formulate a fermentation medium from rice panicle straw (merang) and watermelon rind for producing eco-friendly SCOBY (Symbiotic Culture of Bacteria and Yeast) biofilm. The waste materials were thermally extracted without filtration to retain active solids and subsequently fermented with lactic acid bacteria for 14 days. The fermentation broth was enriched with soybean flour as a nitrogen source and Ziziphus mauritiana leaf extract as an antioxidant additive. Phytochemical screening was conducted using colorimetric reactions analyzed through chromaticity coordinates for flavonoids and grayscale intensity for alkaloids. SCOBY growth was evaluated by measuring biofilm thickness, wet and dry weight, tensile strength, and elongation at break. The results revealed that the combination of these residues provided sufficient nutrients and bioactive compounds to support SCOBY development. The best treatment produced a biofilm with 4.51 mm thickness, 17.49 g wet weight, 3.86 g dry weight, 43.11 MPa tensile strength, and 6.66% elongation. Colorimetric evaluation showed a red chromaticity spectrum for flavonoid presence (dominant wavelength 620 – 625 nm, purity 81.04%), and a clear white grayscale range (220 – 240) for alkaloids. In conclusion, this formulation offers a simple, low-cost approach to converting agricultural waste into functional biofilms. Further investigations are recommended to evaluate the shelf life and potential of liquid SCOBY as a plant immunomodulator and biofilm as organic packaging.